THE EFFECTIVENESS OF PROJECT-BASED LEARNING (PBL) FOR ENGINEERING STUDENTS IN ESP CLASS - Tri Kristianti; Seputro YP, Hariyono (Institut of Shanti Bhuana, 2023)
Teaching English for Specific Purpose (ESP) for non-English Department students is challenging yet exciting since the teacher is required to be more creative in creating a teaching and learning strategy. The use of English for Engineering students is necessary to support the capability of their hard and soft skills. In ESP class, the students learn about vocabulary skills in terms of Engineering and other skills such as writing, reading, speaking, and listening. Those skills are learned correspondingly through some learning activities using applicable teaching strategies such as Project Based Learning (PBL). PBL is introduced as an educational approach focused on the student-centered method. In PBL, the students are given opportunities to explore their capabilities, build their confidence, and improve their motivation to prepare themselves for real work life. This research used a literature review as supportive evidence to measure the efficiency of PBL for teaching Civil Engineering students in semester 1 of the 2021/2022 academic year. Journals, books, and proceeding through computer and electronic databases are used as the basis for data collection. The result found that PBL is an effective and interesting approach that is suitable for teaching Engineering Students compared to traditional and lecture-based approaches. Moreover, PBL is appropriate to gain extensive knowledge of Civil Engineering concepts through intriguing learning activity that enhances the student’s confidence and motivation for real-world projects in the future.